NORMATIVE REGULATION OF LIFE AND HEALTH PHILOSOPHICAL ASPECTS - Sona DAVTYAN (Main Issues Of Pedagogy And Psychology, 2021)
The article discusses some philosophical issues of life and health. The content of bioethics is not limited to finding out which approaches to solving problems related to human life and health are more effective, liberal or conservative. Conservatism stems from the basic premise that human life is an absolute, indisputable value. From the point of view of bioethics, the discovery of the humanitarian potential of liberal values ??is possible only in the conditions of avoiding the extremes of moral relativism, one-sided naturalism, as well as establishing a reasonable balance between conservative and liberal values.